An acoustic microscope for microflaw inspection and subsurface imaging - Litniewski, J. (Archives of Acoustics, 2001)
The representation of an ultrasonic signal coming from the interior of a material using A mode, i.e., a single line of time behaviour, is widely applied in ultrasonic flaw inspection. Much more information on the material can be gained by creating an image in the B representation mode from a large number of A-scan lines. The use of high-frequency ultrasound for creating B-scan images permits the imaging and examination of material structures and inhomogeneities which used to be invisible to date, down to the depth of several millimeters under the sample surface. This paper describes a laboratory model of an acoustic microscope designed for imaging material interior using the B-scan representation mode. The microscope works in the frequency range of 20-70 MHz where images are created on the computer monitor screen or printed out using a video copy processor. On the one hand, the application of the microscope signal processing methods permit the image quality and resolution to be improved, and, on the other, they allow the acoustic properties of materials to be measured. The signal is processed for the purpose of reducing grain noise and eliminating the effects of image representation on a screen with low dynamics compared with the dynamics of the signal. Attempts were also made to find the characteristic properties of the medium under study based on a comparison of the frequency compositions of ultrasound pulses penetrating samples with different grain sizes and attenuation.